Evidence of maternal provisioning of alkaloid-based chemical defenses in the strawberry poison frog Oophaga pumilio - Stynoski, Jennifer Lynn (2014)
Many organisms use chemical defenses to reduce predation risk. Aposematic dendrobatid frogs sequester alkaloid-based chemical defenses from a diet of arthropods, but research on these defenses has been limited to adults. Herein, we investigate chemical defense across development in a dendrobatid frog, Oophaga pumilio. This species displays complex parental care: at hatching, mothers transport tadpoles to phytotelmata, and then return to supply them with an obligate diet of nutritive eggs for about six weeks. We collected eggs, tadpoles, juveniles, and adults of O. pumilio, and detected alkaloids in all life stages. The quantity and number of alkaloids increased with frog and tadpole size. We did not detect alkaloids in the earliest stage of tadpoles, but alkaloids were detected as trace quantities in nutritive eggs and as small quantities in ovarian eggs. Tadpoles hand-reared with eggs of an alkaloid-free heterospecific frog did not contain alkaloids. Alkaloids that are sequestered from terrestrial arthropods were detected in both adults and phytotelm-dwelling tadpoles that feed solely on nutritive eggs, suggesting that this frog may be the first animal known to actively provision post-hatch offspring with chemical defenses. Finally, we provide experimental evidence that maternally derived alkaloids deter predation of tadpoles by a predatory arthropod.